An LES Investigation of Flow Field Around the Cuboid Artificial Reef at Different Angles of Attack - Jie Dai; Qianshun Xu; Yiqing Gong; Yang Lu; Xinbo Liu; Jingqiao Mao (Journal of Marine Science and Engineering)
The placement of artificial reefs (ARs) significantly influences local hydrodynamics and nutrient transport, both of which are crucial for enhancing marine ecosystems and improving marine habitats. Large eddy simulations (LESs) are performed to study the flow field around a cuboid artificial reef (CAR) with three inflow angles (<semantics>α</semantics> = 0°, 45°, and 90°). The numerical method is successfully validated with experimental data, and a reasonable grid resolution is chosen. The results demonstrate that the case with an inflow angle of 45° exhibits superior flow field performance, including the largest recirculation bubble length and the maximum volumes for both the upwelling and wake regions. Stronger turbulence is also observed around the CAR at this inflow angle, attributed to the intensified shear layer. The instantaneous flow features torn horseshoe vortices and rollers shed from the shear layer, which further develop into hairpin vortices.